Effects of Size and Specific Surface Area of Boron Nitride Particles on the Crystallization of Bacterial Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate). Issue 1 (12th July 2013) - Puente, Jorge Arturo Soto; Esposito, Antonella; Chivrac, Frédéric; Dargent, Eric; Kovačević, Vera
Summary Three different grades of Boron Nitride (BN) powder (BN NX1, BN NX5 and BN HCV) having different mean particle size (0.7 to 11 μm) and specific surface area (16 to 40 m2 · g−1) were used as nucleating agents for poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) at a fixed concentration of 2 wt %. Polarized Optical Microscopy (POM) observations, coupled to Differential Scanning Calorimetric (DSC) measurements, allowed to monitor both the isothermal and non‐isothermal crystallization of neat and nucleated PHBVs. It was found that the addition of BN to PHBV modifies the mechanisms of crystallization by starting it at lower supercooling degrees and reducing the half‐crystallization time. This work proved that DSC can replace POM whenever POM does not allow to estimate directly the average linear growth rate of the spherulites during crystallization. The Hoffman‐Lauritzen theory was used to explain the effects of the addition of different grades of BN on PHBV crystallization. As a result, a transition from growth regime III to the growth regime II could be observed for nucleated PHBVs, no matter the grade of BN added. It was evidenced that the coupling between the amorphous and the crystalline phase is modified by the presence of the BN particles. In particular, for a given concentration of nucleating agent, it is the mean size and the specific surface area of BN particles that affect PHBV crystallization.